The Emergence of Mupirocin Resistance among Staphylococcus aureus in a Tertiary Care Hospital in South India: The Necessity for Routine Susceptibility Testing - Abirami lakshmy Jayachandran; Balan Kandasamy (Medical Laboratory Technology Journal, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is difficult to treat, causing considerable morbidity and mortality. Nasal carriage of MRSA can occur both in healthcare workers and patients. Mupirocin is used as a topical agent for the eradication of such isolates. The present study aims to study the prevalence of mupirocin resistance among the MRSA and MSSA (Methicillin-sensitive Staphylococcus aureus) isolates. A total of 148 Staphylococcus aureus isolates were tested. Antibiotic susceptibility testing was done by Kirby Bauer disc diffusion method for amoxicillin, penicillin, cotrimoxazole, clindamycin, mupirocin(5 µg and 200 µg discs for low and high-level resistance), erythromycin, gentamicin and linezolid. MRSA isolates were detected by cefoxitin disc diffusion and Mec A detection by PCR (Polymerase Chain Reaction). MRSA was detected among 44 (29.7%) of the isolates. Among MSSA, good susceptibility was observed for cotrimoxazole 89 (85.5%) and clindamycin 92 (88.4%). An overall mupirocin resistance of 12(8.1%) was observed, with high-level resistance at 4 (2.7%) and low-level resistance at 8 (5.4%).The mupirocin resistance pattern between MRSA and MSSA was not statistically significant (p=0.1833). The emergence of mupirocin resistance highlights the necessity for creating cognizance among clinicians before prescribing mupirocin. In eradicating nasal carriage of MRSA, all the isolates should always be tested for mupirocin susceptibility to prevent the selection and spread of drug-resistant isolates.